1988
DOI: 10.1128/mcb.8.1.138
|View full text |Cite
|
Sign up to set email alerts
|

Transformation by the src oncogene alters glucose transport into rat and chicken cells by different mechanisms.

Abstract: Transformation of both rat and chicken fibroblasts by the src oncogene leads to a four-to fivefold increase in the rate of glucose transport and in the level of the glucose transporter protein. We have previously shown that, with chicken embryo fibroblasts, transformation leads to a reduction in the rate of degradation of the transporter, with little or no increase in the rate of its biosynthesis. We now show that, with the rat-1 cell line, the opposite result was obtained. src-induced transformation led to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
1

Year Published

1989
1989
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 29 publications
4
54
1
Order By: Relevance
“…Expression of v-Src decreased the proportion of cells in the G 0 /G 1 phase Rat-1 ®broblasts expressing a temperature sensitive (ts) mutant of Rous sarcoma virus (ts LA 29 Rat-1) are transformed at the permissive temperature (358) and display normal morphology and behaviour at the restrictive temperature (39.58) (Welham et al, 1990;White and Weber, 1988). To study the e ect of v-Src on cell cycle control, we compared the growth characteristics of ts LA 29 Rat-1 with non transfected Rat-1 cells at both temperatures in medium containing 5% serum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression of v-Src decreased the proportion of cells in the G 0 /G 1 phase Rat-1 ®broblasts expressing a temperature sensitive (ts) mutant of Rous sarcoma virus (ts LA 29 Rat-1) are transformed at the permissive temperature (358) and display normal morphology and behaviour at the restrictive temperature (39.58) (Welham et al, 1990;White and Weber, 1988). To study the e ect of v-Src on cell cycle control, we compared the growth characteristics of ts LA 29 Rat-1 with non transfected Rat-1 cells at both temperatures in medium containing 5% serum.…”
Section: Resultsmentioning
confidence: 99%
“…We report here a further examination of the mitogenic action of v-Src, exploiting the rapidly reversible activity of the temperature sensitive v-Src mutant, ts LA 29, in Rat-1 cells (Welham and Wyke, 1988;White and Weber, 1988). We found that v-Src transformed cells traversed G 1 more rapidly and did not exit cycle e ciently in response to inhibitory stimuli.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Cell culture ts LA 29 Rat-1 cells (White and Weber, 1988) were cultured as described previously (Johnson et al, 1998). To induce quiescence 5 to 10610 5 cells per 9 cm plate or 2.5 to 5610 6 cells per 15 cm plate were seeded at the permissive temperature (358C).…”
Section: Methodsmentioning
confidence: 99%
“…12 Especially, the type 1 glucose transporter (GLUT1) gene is one of the early genes that are activated after transformation of cells with oncogenes such as src, ras or fps. [13][14][15][16][17][18][19][20] An increase of GLUT1 mRNA was found 4-6 h after induction of the p21 c-H-ras oncoprotein, whereas morphologic changes occurred 72-96 h later. 18,21 The facilitative glucose transporter GLUT1 has also been shown to be upregulated in human tumor tissues.…”
mentioning
confidence: 99%